Analisis Pesan Dakwah pada Film Animasi Nussa dan Rara Episode 1-5 - Fitriatin Nadhifah; A. Khairuddin (Maddah : Jurnal Komunikasi dan Konseling Islam, 2021)
There are so many media that can be used to convey da'wah messages such as television, radio, internet and it can also be through print or press media, such as newspapers, magazines, and books. This article aims to describe the message of da'wah contained in the animated film Nussa and Rara episodes 1-5. The research method used in this research is qualitative. This approach is often used to examine messages in the media which focuses on literature research which will produce a conclusion about language style, content tendencies, writing, layout, illustrations and so on. The results show that there are three messages of da'wah, namely: First, the message of faith in the form of belief in Allah SWT that Allah SWT will always protect him, believe that Allah SWT will always answer the prayers of his servants, and believe that everything that begins with basmalah then Allah SWT will always protect they. Second, the moral message in the form of Nussa's teachings to Rara to always be polite and courteous. Third, the shari'ah message is in the form of adab before eating that the Prophet has taught and starting everything with basmalah